Organizational Improvement and Accountability Lessons for Education from Other Sectors - Stecher, Brian M. (RAND Corporation, 2004)
Examines five accountability models--two from the manufacturing sector; a performance incentive model used in the evaluation of job training programs for the poor; accountability in the legal sector; and accountability in health care as shown by clinical practice guidelines, use of statistical risk-adjustment methods, and the public reporting of health performance measures. The authors summarize the models' effectiveness and draw lessons for implementing the No Child Left Behind Act.